Answer:
1500
Step-by-step explanation:
<em>The</em><em> </em><em>answer</em><em> </em><em>is</em><em> </em><em>parallel</em><em>.</em>
<em>hope</em><em> </em><em>this</em><em> </em><em>will</em><em> </em><em>help</em><em> </em><em>u</em><em>.</em><em>.</em><em>.</em><em>.</em>
Answer:
3/4
Step-by-step explanation:
Because the total homework would be 25/25
![\frac{25}{25}-\frac{10}{25} =\frac{15}{25}](https://tex.z-dn.net/?f=%5Cfrac%7B25%7D%7B25%7D-%5Cfrac%7B10%7D%7B25%7D%20%3D%5Cfrac%7B15%7D%7B25%7D)
15/20 can be reduced to 3/4
To factor both numerator and denominator in this rational expression we are going to substitute
![n^{2}](https://tex.z-dn.net/?f=n%5E%7B2%7D%20)
with
![x](https://tex.z-dn.net/?f=%20x%20)
; so
![n^{2} =x](https://tex.z-dn.net/?f=n%5E%7B2%7D%20%3Dx)
and
![n ^{4} = x^{2}](https://tex.z-dn.net/?f=n%20%5E%7B4%7D%20%3D%20%20x%5E%7B2%7D%20%20)
. This way we can rewrite the expression as follows:
![\frac{n^{4}-11n^{2} +30 }{n^{2}-7n^{2} +10 } = \frac{ x^{2} -11x+30}{ x^{2} -7x+10}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bn%5E%7B4%7D-11n%5E%7B2%7D%20%2B30%20%7D%7Bn%5E%7B2%7D-7n%5E%7B2%7D%20%2B10%20%7D%20%3D%20%20%5Cfrac%7B%20x%5E%7B2%7D%20-11x%2B30%7D%7B%20x%5E%7B2%7D%20-7x%2B10%7D%20)
Now we have two much easier to factor expressions of the form
![a x^{2} +bx+c](https://tex.z-dn.net/?f=a%20x%5E%7B2%7D%20%2Bbx%2Bc)
. For the numerator we need to find two numbers whose product is
![c](https://tex.z-dn.net/?f=c)
(30) and its sum
![b](https://tex.z-dn.net/?f=b)
(-11); those numbers are -5 and -6.
![(-5)(-6)=30](https://tex.z-dn.net/?f=%28-5%29%28-6%29%3D30)
and
![-5-6=-11](https://tex.z-dn.net/?f=-5-6%3D-11)
.
Similarly, for the denominator those numbers are -2 and -5.
![(-2)(-5)=10](https://tex.z-dn.net/?f=%28-2%29%28-5%29%3D10)
and
![-2-5=-7](https://tex.z-dn.net/?f=-2-5%3D-7)
. Now we can factor both numerator and denominator:
![\frac{ x^{2} -11x+30}{ x^{2} -7x+10} = \frac{(x-6)(x-5)}{(x-2)(x-5)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20x%5E%7B2%7D%20-11x%2B30%7D%7B%20x%5E%7B2%7D%20-7x%2B10%7D%20%3D%20%5Cfrac%7B%28x-6%29%28x-5%29%7D%7B%28x-2%29%28x-5%29%7D%20)
Notice that we have
![(x-5)](https://tex.z-dn.net/?f=%28x-5%29)
in both numerator and denominator, so we can cancel those out:
![\frac{x-6}{x-2}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx-6%7D%7Bx-2%7D%20)
But remember than
![x= n^{2}](https://tex.z-dn.net/?f=x%3D%20n%5E%7B2%7D%20)
, so lets replace that to get back to our original variable:
![\frac{n^{2}-6 }{n^{2}-2 }](https://tex.z-dn.net/?f=%20%5Cfrac%7Bn%5E%7B2%7D-6%20%7D%7Bn%5E%7B2%7D-2%20%7D%20)
Last but not least, the denominator of rational expression can't be zero, so the only restriction in the variable is
![n^{2} -2 \neq 0](https://tex.z-dn.net/?f=n%5E%7B2%7D%20-2%20%5Cneq%200)
![n^{2} \neq 2](https://tex.z-dn.net/?f=%20n%5E%7B2%7D%20%20%5Cneq%202)